A CREATION OF THE LINGUISTIC ONTOLOGY BASED ON ASTRUCTURED ELECTRONIC ENCYCLOPEDIC RESOURCE - Mykhailiuk, Anton; Mykhailiuk, Olena; Pylypchuk, Oleksiy; Tarasenko, Volodymyr (International Journal of Computing, 2014)
Solving the problem of intelligent information retrieval requires the use of additional specialized linguistic resources. One of such type of resources is a linguistic ontology of a subject field. The paper considers an approach to develop software for an automatic creation of an ontological knowledge base by the converting structured encyclopedic resource into appropriate ontology’s objects. The procedures of creation of the ontology entities base, the hierarchy of entities and the network of associative links are considered. Qualitative and quantitative analysis of the produced experimental ontology based on Ukrainian part of Wikipedia is investigated.